Proteomic Analysis of Placental Mitochondria Following Trophoblast Differentiation - Fisher, Joshua J.; McKeating, Daniel R.; Cuffe, James S.; Bianco-Miotto, Tina; Holland, Olivia J.; Perkins, Anthony V. (Frontiers in Physiology, 2019)
As gestation proceeds the human placenta is in a constant state of renewal and placental debris is released into the maternal circulation where it can trigger adverse physiological and immunological responses. Trophoblast cells of the placenta differentiate from mononuclear cytotrophoblast cells to fuse and form the syncytiotrophoblast, a multinuclear layer that covers the entire surface of the placenta. As part of this process there are significant changes to cellular cytoskeletal organisation and organelle morphology. In this study we have examined the molecular changes that occur in mitochondria from these two cellular compartments and identified differential expression of key proteins that underpin changes in mitochondrial morphology, metabolism and function. Mitochondria were isolated for term placental tissue and separated according to size and density by sequential differential centrifugation. Isolated mitochondrial populations were then subjected to proteomics using HPLC separation of peptides and MS identification. Differential expression of proteins of interest was confirmed by western blots. Using a bioinformatics approach we also examined published protein databases to confirm our observations. In total 651 proteins were differentially regulated in mitochondria from cytotrophoblast versus syncytiotrophoblast. Of these 29 were statistically significant and chosen for subsequent analysis. These included subunits of ATP synthase that would affect ATP production and cristae structure, carbohydrate metabolising enzymes phospoenolpyruvate carboxykinase-2, pyruvate carboxylase and pyruvate dehydrogenase, fatty acid metabolising enzyme acyl-CoA dehydrogenase, stress responses such a glucose regulated protein-78 and protein disulfude isomerase, and mitochondrial dynamics proteins mitofusin 1 and 2. Placental cell biology and mitochondrial function is central to the pathogenesis of many gestational disorders such as preeclampsia, pre-term birth, fetal growth restriction and gestational diabetes. These studies show important shifts in mitochondrial metabolism and dynamics post trophoblast differentiation and provide key molecular targets for study in pathological pregnancies.